Green Loyalty – Empirical Experience from a Systematic Literature Review - I Made Surya Prayoga; I Gusti Ayu Ketut Giantari; Putu Yudi Setiawan; I Gusti Ngurah Jaya Agung Widagda K (Jurnal Ilmu Sosial dan Humaniora, 2024)
Our research aims to analyze the factors determining green loyalty based on a systematic literature review (SLR) according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement. We asked three research questions: The main factors that determine green loyalty, The most widely used theories in building empirical research models on green loyalty, and how often do traditional elements, such as values, image, knowledge, satisfaction, trust, practice, and quality perceived, emerges in empirical research on eco-loyalty. The SLR search of the three databases yielded 571 publications. The snowballing method produced 78 records. After removing duplicates, 330 records were obtained, and in the final stage, only 19 articles were used in the systematic literature review. Based on the analysis results, seven main factors influence green loyalty. The Social Exchange Theory is the grand theory most widely used in building research models. The implications of this research will explain how green loyalty is currently a very urgent and important topic to research, as well as make it easier for researchers to see gaps as opportunities in building research models, especially those related to green loyalty.